Demand and consumption patterns of banana in Tanzania - William George (Discover Food)
Abstract Bananas (Musa spp.) are a key dietary staple and income source in Tanzania, with varying demand patterns across urban and rural areas. This study examines banana demand and consumption patterns in Tanzania, addressing a gap in the literature across different contexts. Cross-sectional data from 2021 and time series data from 2000 to 2021 were used. Dynamic econometric models, including the Constant Elasticity of Demand framework and log-linear regression, assess the impact of price, income, and consumer preferences on banana demand. The findings reveal a negative price elasticity of demand for bananas, ranging from −0.110 to −0.130, statistically significant at the 10% level. Cross-price elasticities show substitution effects with cassava (0.06–0.08) and sweet potatoes (0.24). Income elasticity is positive (0.040–0.070) and significant. Regional differences in price elasticity are observed, with urban consumers showing a range of −0.330 to −1.150, and rural consumers between −0.480 and −1.010. Income elasticities are positive and significant in both regions. The study highlights that banana consumption is influenced by price, income, and shifting consumer preferences. It offers policy recommendations to strengthen the banana value chain and improve food security in Tanzania.